PELAKSANAAN PENDIDIKAN AGAMA ISLAM PADA SEKOLAH LUAR BIASA DI PROPINSI BALI - A.M. Wibowo (IAIN Pekalongan, 2011)
This paper is the result of a study of the implementationof Education of Islamic Religion in Schools for the Gifted Children inthe province of Bali. Starting from the author’s curiosity about howfar Education of Islamic Religion is existed and integrated in theeducational process in the Schools for the Gifted Children. Religiouseducation is an obligation of schools to meet the equal rights of learnerswith special needs in terms of spiritual fulfillment with other normalstudents. By using a qualitative approach, this study found threethings. Firstly, implementation of Education of Islamic Religion inspecial needs students is still far from ideal. Secondly, professionalcompetence of Education of Islamic Religion’s teachers does notmeet the standards of academic qualifications as like non religiongraduates. Thirdly, the factor inhibiting implementation of the Educationof Islamic Religion in Schools for the Gifted Children is thatEducation of lslamic Religion is still regarded as a second job in theeducation process in the Schools for the Gifted Children